2020
DOI: 10.1101/2020.05.14.097311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analytical and Clinical Comparison of Three Nucleic Acid Amplification Tests for SARS-CoV-2 Detection

Abstract: 16

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 7 publications
6
28
0
Order By: Relevance
“…Our evaluation of three different external RNA control materials demonstrated comparable analytical sensitivity with both the SARS-CoV-2 TMA assay and the SARS-CoV-2 RT-PCR assay, with LOD values of between 83 c/ml of 194 c/ml. These analytical sensitivity values correlate with previously reported LOD values by Smith et al ( 16 ). However, using LOD values as determined by external control material to assess or compare assay performance warrants some caution, as different control materials may give considerably different results for the absolute LOD value ( 16 ), and the reported RNA or DNA stock concentrations of these materials may differ from true concentrations ( 17 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our evaluation of three different external RNA control materials demonstrated comparable analytical sensitivity with both the SARS-CoV-2 TMA assay and the SARS-CoV-2 RT-PCR assay, with LOD values of between 83 c/ml of 194 c/ml. These analytical sensitivity values correlate with previously reported LOD values by Smith et al ( 16 ). However, using LOD values as determined by external control material to assess or compare assay performance warrants some caution, as different control materials may give considerably different results for the absolute LOD value ( 16 ), and the reported RNA or DNA stock concentrations of these materials may differ from true concentrations ( 17 ).…”
Section: Discussionsupporting
confidence: 91%
“…The Cepheid assay has a manufacturer claim of 250 copies/ml for nasopharyngeal swab specimens ( 26 ), and one study demonstrated an even lower LoD of 100 copies/ml ( 25 ). The Hologic assay has a claimed LoD of 0.01 50% tissue culture infective dose (TCID 50 )/ml ( 27 ), and an LoD of 62.5 copies/ml or 1,000 copies/ml was obtained using synthetic RNA reference material or whole inactivated virus, respectively ( 32 ). The higher LoD for stool than upper respiratory specimens may be due to the presence of PCR inhibitors ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used technique is PCR and TMA, that has subsequently been incorporated. The sensitivity and specificity of these techniques is very high, both around 99%, which makes them very useful for diagnosing infection [19].…”
Section: Capacity and Current Value Of The Main Microbiological Technmentioning
confidence: 99%